Parathyroidectomy for primary hyperparathyroidism: The results of a single institution (Annals of Medical Research, 2021)
Aim: Primary hyperparathyroidism (PHPT) is a clinical entity characterized by an excess synthesis of parathormone due to one or more autonomic parathyroid gland. The present study aims to evaluate the outcomes of parathyroidectomies performed due to PHPT.Material and Methods: The results of 52 parathyroidectomies performed due to PHPT between September 2014 and October 2018 were retrospectively evaluated for demographic, clinical, imaging and pathologic characteristics.Results: Fifty-two patients with primary hyperparathyroidism were included in the study. The mean age of the patients was 50±14.5 years. Forty-three (82.9%) patients were female and 9 (17.4%) were male. The most common complaints at admission were generalized muscle and bone pain in 13 patients (15.3%). In 2 patients (3.8%) osteoporosis and another 2 (3.8%) patients, nephrolithiasis was identified. Thirty- five (67.3%) patients had no complaints. The mean preoperative calcium level was 11.21±0.88 mg/dl. Mean preoperative phosphate level was 2.58±0.72 mg/ dl. Mean preoperative parathormone level was 278.65±317.67 pg/ml. Technetium 99m-sestamibi scintigraphy was obtained for 41 patients. Cervical ultrasonography was performed in 43 patients. The surgical localization of the parathyroid adenoma showed that the accuracy of ultrasonography was 60.4% whereas the accuracy of Technetium 99m-sestamibi scintigraphy was 80.4%. Three of the 12 (25%) patients with no localization in ultrasonography had parathyroid hyperplasia as the pathologic diagnosis. There were two patients in whom ultrasonography and scintigraphy could not localize the pathologic parathyroid tissue and all of them (100%) were found to have parathyroid hyperplasia as the pathologic evaluation. Pathologic evaluation of the surgical specimens showed that there was adenoma in 40 patients (76.9%), hyperplasia in 5 (9.6%), normal parathyroid tissue in 5 (9.6%), tumor with undetermined biologic potential in 1 patient (1.9%) and adenomatous parathyroid tissue in 1 patient (1.9%). In fifteen patients (28.8%) concomitant total thyroidectomy, right lobectomy in 7 patients (13.4%)and left lobectomy in 4 patients (7.6%) were performed.Conclusion: Parathyroid adenoma can be localized in places other than the expected locations; despite the advances in imaging technologies. Surgeons experience and accurate localization before the operation are important for a successful parathyroid operation. If scintigraphy and ultrasonography cannot localize the pathologic parathyroid tissue, hyperplasia should be suspected.